(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The concept of generosity, deeply rooted in human cultural and moral values, finds vivid expression in the phraseological units of various languages. This study examines the linguistic representation and cultural nuances of generosity in English and Uzbek, focusing on their similarities and differences. By analyzing examples from both languages, it explores how cultural contexts shape the interpretation and use of idiomatic expressions related to generosity. The findings aim to contribute to cross-cultural linguistics and provide insights into the interplay between language, culture, and human values.